Bioactive compounds and protective effect of red and black rice brans extracts in human neuron-like cells (SH-SY5Y). (November 2018) - Vargas, Carolina Galarza; da Silva Junior, Jeferson Delgado; Rabelo, Thallita Kelly; Moreira, José Cláudio Fonseca; Gelain, Daniel Pens; Rodrigues, Eliseu; Augusti, Paula Rossini; Rios, Alessandro de Oliveira; Flôres, Simone Hickmann
Abstract: Rice bran is obtained from the rice polishing process, and this by-product contains many bioactive compounds. In this study, the composition of phenolic compounds from red and black rice brans was determined by HPLC−DAD−MS. Additionally, the neuroprotective ability of these brans in SH-SY5Y cells insulted with hydrogen peroxide (H2 O2 ) was evaluated. The phenolic constituents of rice bran were separated into hydrophilic and pellet fractions. The major phenolic compound in both samples was ferulic acid. Cyanidin 3-glucoside was the main anthocyanin in black rice bran. The hydrophilic and pellet fractions showed a protective effect (38–94%) on SH-SY5Y cells insulted by H2 O2 in DCFH-DA assay. No extract showed cytotoxicity in the SRB assay. These results suggest a neuroprotective effect of red and black rice brans extracts due to their high antioxidant capacity, along with the absence of cytotoxicity. Thus, they may potentially be used as sources of bioactive compounds. Graphical abstract: Highlights: Ferulic acid was predominantly phenolic compound in red and black rice bran. Anthocyanins were the main compounds in black rice bran. Rice bran extracts showed neuroprotective effect due their antioxidant capacity. The black and red bran extracts do not showed cytotoxicity in the SRB assay.